Strategi Optimalisasi Pemanfaatan Aset Daerah dalam Mewujudkan Pembangunan Berkelanjutan - Khaerunisa, Ratu Nazwa; Apud Saepudin, Eli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Optimal use of regional assets is one of the important keys in realizing sustainable development at the regional level. Regional assets in the form of land, buildings and natural resources can be used to support increasing regional original income (PAD), improving the quality of infrastructure and supporting community welfare. This research aims to examine strategies for optimizing the use of regional assets in order to support sustainable development goals. This research uses a qualitative analysis approach by exploring various literature sources and case studies from areas tht are successful in asset management. The main findings show that an effective regional asset utilization strategy includes a balanced economic, social and environmental approach. The application of information technology in asset management and increasing human resource capacity are important factors in optimizing regional asset management. In addition, asset utilization must pay attention to the principles sustainability, avoid excessive exploitation of natural resources, and prioritize the long-term interests of society. With the right strategy,regional asset management can contribute significantly to achieving sustainable development goals involving economic, social and environmental aspects.